(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
Vamin A is a vital fat-soluble nutrient that plays a central role in maintaining overall health, with particularly significant effects on skin structure and function. Its biologically active form, retinoic acid, exerts its effects by binding to nuclear receptors—retinoic acid receptors (RARs) and retinoid X receptors (RXRs)—which regulate the expression of genes involved in skin cell proliferation, differentiation, and repair. Through these molecular mechanisms, vitamin A ensures proper epidermal renewal, maintains the integrity of the skin barrier, stimulates collagen production, and supports wound healing. These processes explain its therapeutic value in dermatology for the treatment of conditions such as acne, hyperkeratinization disorders, photoaging, and other skin pathologies.